Trends in prevalence of gestational diabetes and perinatal outcomes in Catalonia, Spain, 2006 to 2015: the Diagestcat Study. Issue 5 (16th April 2019) - Gortazar, Lucía; Flores‐Le Roux, Juana A.; Benaiges, David; Sarsanedas, Eugènia; Payà, Antonio; Mañé, Laura; Pedro‐Botet, Juan; Goday, Alberto
Abstract: Background: No recent epidemiologic studies on gestational diabetes mellitus (GDM) have been conducted in Spain. The present study aimed to explore trends in the prevalence of GDM and ascertain whether the risk of adverse perinatal outcomes changed between 2006 and 2015 in Catalonia. Methods: In this population‐based study, all hospital admissions for singleton births in Catalonia for the period 2006 to 2015 were collected from the Spanish Minimum Basic Data Set. Cases of GDM were identified from hospital delivery discharge reports using ICD‐9‐CM codes. Data regarding maternal characteristics and perinatal outcomes were analysed. Crude and age‐adjusted annual prevalences were calculated. The Poisson regression model was used to assess trends in prevalence and perinatal outcomes, adjusted for age and smoking habit; however, they could not be adjusted for body mass index (BMI) and ethnicity. Results: Data from 743 762 deliveries were collected. GDM prevalence over the study period was 4.80% (95% CI 4.75‐4.85%). Crude GDM prevalence rose from 3.81% (95% CI 3.67‐3.95%) in 2006 to 6.53% (95% CI 6.33‐6.72%) in 2015 ( P < 0.001). Women with GDM showed a stable trend in rates of preeclampsia (2.56%), prematurity (15.7%), and large‐for‐gestational age (LGA) newborns (18.3%), whereas a lower rate of macrosomia was observed during the study period (from 9.16% to 7.84%). Caesarean deliveries rose from 28% to 31%; however, significance was lost after adjustment. Conclusions: The prevalence of GDM in Catalonia almost doubled between 2006 and 2015. During the study period, the frequency of macrosomia decreased whereas pre‐eclampsia, prematurity, LGA, and age‐adjusted Caesarean rates remained stable.